Folliculin Interacting Protein 1 (FNIP-1) expression and capillary density in gastrocnemius muscle tissue of mice after biological maturation period - Sinta Ayu Choiriyah; Bambang Purwanto; Viskasari Pintoko Kalanjati; Raden Argarini; Anisah Rosydiyah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The biological maturity period is the time or tempo of progress toward adulthood or maturity. The hormonal fluctuations play an important role in changing the characteristics of human body tissues during the biological maturity period. However, changes in tissue characteristics during biological maturity period have not been revealed. Skeletal muscle tissue is one of those believed to experience changes. Muscle fibers are thought to experience switching types from type 2 muscle fibers to type 1 muscle fibers. The transition of muscle fibers from type 2 to type 1 requires miR-499 activity from the expression of the Myh7b gene. MiR-499 directly inhibits FNIP-1. However, the biological maturity period of changing FNIP-1 expression has not been confirmed.